Report on proposed e interior design of True Religion Brand Jeans Boutique for Bread And Butter Sdn Bhd at Lot 201, Level 2, Avenue K, Kuala Lumpur / Izwani Mohd Shah - Mohd Shah, Izwani (Faculty of Architecture, Planning and Surveying, 2010)
A final year student of diploma course in Interior Design is necessary to organize one final year project. The project that had been selected for the final project is to propose New Interior Design of True Religion Brand Jeans Boutique for Bread And Butter Sdn Bhd at Lot 201, Level 2, Avenue K, Kuala Lumpur. The reason to propose this project is because there is no True Religion Brand Jeans Boutique in Malaysia. The target market for the users of this True Religion Brand Jeans product are men, women, boys and girls from all ages and classes. The product includes footwear, headwear, swimwear, eyewear, hosiery, socks, and fragrance. Thereafter, a plan was proposed to organize a boutique design that may interest and fulfil the public demand, needs for both of client and customers. From the study and observation conducted on the product and the location, the information and details gathered was used as a guideline to prepare the design. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally. For this propose project, site at Avenue K was choose after had done survey in few places and it seems that the site chosen gives good impact and the surroundings suit the business purpose.